dShark: A General, Easy to Program and Scalable Framework for Analyzing In-network Packet Traces - Yu, Da; Zhu, Yibo; Arzani, Behnaz; Fonseca, Rodrigo; Zhang, Tianrong; Yuan, Lihua; Deng, Karl (NSDI 2019, 2019)
Distributed, in-network packet capture is still the last resort for diagnosing network problems. Despite recent advances in collecting packet traces scalably, effectively utilizing pervasive packet captures still poses important challenges. Arbitrary combinations of middleboxes which transform packet headers make it challenging to even identify the same packet across multiple hops; packet drops in the collection system create ambiguities that must be handled; the large volume of captures, and their distributed nature, make it hard to do even simple processing; and the one-off and urgent nature of problems tends to generate ad-hoc solutions that are not reusable and do not scale. In this paper we propose dShark to address these challenges. dShark allows intuitive groupings of packets across multiple traces that are robust to header transformations and capture noise, offering simple streaming data abstractions for network operators. Using dShark on real-time packet captures from a major cloud provider, we show that dShark makes it easy to write concise and reusable queries against distributed packet traces that solve many common problems in diagnosing complex networks. Our evaluation shows that dShark can analyze production packet traces with more than 10 Mpps throughput on a commodity server, and has near-linear speedup when scaling out on multiple servers.